2007
DOI: 10.1172/jci32033
|View full text |Cite
|
Sign up to set email alerts
|

The thiazide-sensitive Na-Cl cotransporter is regulated by a WNK kinase signaling complex

Abstract: The pathogenesis of essential hypertension remains unknown, but thiazide diuretics are frequently recommended as first-line treatment. Recently, familial hyperkalemic hypertension (FHHt) was shown to result from activation of the thiazide-sensitive Na-Cl cotransporter (NCC) by mutations in WNK4, although the mechanism for this effect remains unknown. WNK kinases are unique members of the human kinome, intimately involved in maintaining electrolyte balance across cell membranes and epithelia. Previous work show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 40 publications
6
141
1
Order By: Relevance
“…The activation of NCC by WNK3-18a has been corroborated by other groups (7,32). In the present study, we tested the effects of all potential WNK3 variants on the activity of these cotransporters.…”
Section: Effects Of Wnk3 Variants On the Sodium-coupled Chloride Cotrsupporting
confidence: 66%
See 1 more Smart Citation
“…The activation of NCC by WNK3-18a has been corroborated by other groups (7,32). In the present study, we tested the effects of all potential WNK3 variants on the activity of these cotransporters.…”
Section: Effects Of Wnk3 Variants On the Sodium-coupled Chloride Cotrsupporting
confidence: 66%
“…WNKs are complex kinases that are still poorly understood, but it seems that minimal disruption of their primary structures can prevent or switch their mode of action toward a particular target (13,23,29,32). For instance, although the effect of WNK3-18a on NCC is clearly dependent on its kinase activity, Yang et al (32) have shown that a similar effect can be obtained by the WNK3 carboxyl terminal domain in the complete absence of the kinase domain. For this reason, all WNK variants used in this study were completely sequenced to avoid any unwanted mutations that could result in truncated or altered proteins.…”
Section: C604mentioning
confidence: 99%
“…Similar to WNK4 regulation on NCC (29,32,33), WT-WNK4 inhibits TRPC3 activity by regulating its surface abundance, which was dependent on the kinase activity of WNK4. Similarly, parallel to the effect on NCC, the aberrant regulation by WNK4 Q562E increased the surface expression of TRPC3 and thus raised [Ca 2+ ] i .…”
Section: Discussionmentioning
confidence: 97%
“…Hence, regulatory pathways of renal ion transport that have been revealed by the discovery of WNK4 mutations in PHAII patients provide valuable insights into the pathogenesis of hypertension. To date, fluid retention due to the increased Na + and fluid reabsorption by the kidney through increased activity of NCC is considered as the sole mechanism for the increased blood pressure in PHAII patients harboring the WNK4 Q562E mutation (5,(27)(28)(29). However, the expression of WNK4 in diverse extrarenal tissues (11) suggests that an additional pathway may contribute to the elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike WNK4, WNK3 stimulates NCC activity in Xenopus oocytes. 51,52 WNK3 and WNK4 share a high degree of amino acid identity within the kinase domain but a much lower degree of amino acid identity in the amino and carboxyl terminal domains. San-Cristobal et al 53 reported that amino terminus of WNK3 or WNK4 plays an important role in regulation of NCC activity.…”
Section: Discussionmentioning
confidence: 99%